Proceedings of the 13th UK Heat Transfer Conference UKHTC2013 - Markides,CN; Heyes,AL; Childs,PRN (DEG Imperial College London, 2014)
The UK Heat Transfer Conference is now in its 29th year and it remains the premier UK conference for the local and international heat transfer community to meet and present their work. Heat transfer is a critical process in innumerable industrial and commercial processes and despite decades of high quality research there remain many challenges. However, with the desire to move to a more sustainable and low carbon energy future greater emphasis is being placed on the provision of and effective use of heat. The organisers decided to reflect this by enlarging the scope of the conference to explicitly include heat as well as heat transfer. The response was excellent as can be discerned from the list of abstracts presented herein. On the pages that follow we present approximately 100 papers from 24 nations and 5 continents. We are delighted by the level of interest shown in the conference and we hope to make this the best UK Heat Transfer Conference to date.